Pelatihan jurnalistik pada redaktur majalah sekolah Serambi Al-Muayyad - Farida Yufarlina Rosita (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
School magazines are a medium for students to practice and develop their journalistic potential. A student must have qualified journalistic knowledge to produce good writing in a magazine. For this reason, training and assistance in magazine writing are necessary so that school magazines continue to exist and are of higher quality. One school that has a school magazine is MA Al-Muayyad Surakarta. Journalism training is essential at this school because many students have not developed their writings properly. The methods used in this training are interviews, presentations, discussions, and article writing training. This training was held in April 2018. This training activity provides good benefits, especially for the training participants, because before the training was held, most of the magazine's contents took sources from the internet. However, after the training, the students' writing became original, the language used got better, and the rubric content more diverse